When and for Whom Implicit Partner Evaluations Predict Forgiveness. Issue 5 (July 2021) - Faure, Ruddy; Righetti, Francesca; Larson, Grace; Cuellar, Maria Fernanda; Koutsoumpis, Antonis; Zwicker, Maria; Hofmann, Wilhelm
Recent work suggests that implicit partner evaluations have long-term implications for relationship success. However, little evidence shows whether and under which conditions implicit partner evaluations affect relationship maintenance processes in daily life, especially those exhibited in situations that may be highly decisive for the fate of the relationship, such as when partners hurt each other. Drawing upon dual-process theories, we predicted that, when executive control is limited—either as a trait or a state—people's implicit partner evaluations influence forgiveness toward their partner. Results revealed that when temporarily impairing people's executive control with an experimental manipulation (Study 1), or for people with lower trait executive control (Study 2), more positive implicit partner evaluations were associated with more forgiveness, both in laboratory settings and in an 8-day diary. These findings highlight the importance of implicit partner evaluations under specific, yet common, conditions for promoting reparatory responses that are key to relationship success.